INFLUENCE OF UNIPOLAR MAGNETIC FIELD ON BIOLOGICAL OBJECTS - V. I. Shalatonin; G. G. Vereshchako (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The experiments on the effect of unipolar magnetic field (MF) on the germination and growth of wheat seeds were carried out. It was shown that that the shielding of a unipolar magnet by polyethylene film changes the biological activity of the magnetic field.